昭和基地における地磁気観測基線値とセンサーの傾斜の変動 - 有田, 真; アリタ, シン; 井, 智史; イ, トモフミ; 仰木, 淳平; オオギ, ジュンペイ; 高橋, 幸祐; タカハシ, コウスケ; 門倉, 昭; カドクラ, アキラ; 源, 泰拓; ミナモト, ヤスヒロ; et al. (国立極地研究所, 2020)
南極の昭和基地では，基線値（絶対観測値と連続観測値との差）が特に夏期間において顕著な変化を示す．この変化の要因としては，例えば重機のような磁性体によるノイズや磁力計センサーの傾斜変動や温度変化といった設置環境の変化が考えられる．磁力計センサーの傾斜変動が夏期間の基線値変化に及ぼす影響を調査するために，電子水管傾斜計を用いて傾斜変化を連続観測するとともに，絶対観測を通常より高頻度で実施した（2013 年1 月～2 月，2013 年11 月～2014 年2 月）．調査の結果，東西方向で30 秒角から50 秒角程度，南北方向で10秒角程度の顕著な傾斜変化があることが判明した．基線値変化には傾斜変化が大きく寄与していることが分かり，傾斜変化の基線値変化への寄与率は最大で，D成分で60% から100%，H 成分とZ 成分で30% から40% と推定された． At Syowa Station, Antarctica, the baseline values, or the difference between the absolute and continuous measurements, vary relatively significantly in summer. They are possibly due to artificial disturbances from magnetized objects, and/or changes of the instrumental environment such as involving the tilt and temperature of the sensor for continuous observations. To evaluate the effect of the sensor tilt, we continuously monitored its behavior with electronic tiltmeters over two successive summer seasons (Jan.-Feb. 2013, Nov. 2013-Feb. 2014), while also intensifying the frequency of the absolute observation. The variability of the tilt was found such that, its angular changes in the East-West and North-South directions were 30 to 50 and 10 arcseconds, respectively. The observed variations of the baseline values can be attributed primarily to the sensor tilt changes, with its contribution estimated to be up to 60 to 100% for the D component and 30 to 40% for the H and Z components. departmental bulletin paper